2013
DOI: 10.1017/s0007114513002237
|View full text |Cite
|
Sign up to set email alerts
|

Short-term, daily intake of yogurt containing Bifidobacterium animalis ssp. lactis Bf-6 (LMG 24384) does not affect colonic transit time in women

Abstract: The present study investigated the effect of Bifidobacterium animalis ssp. lactis Bf-6 (LMG 24 384) (Bf-6)-supplemented yogurt on colonic transit time (CTT). A triple-blinded, randomised, placebo-controlled, two-period cross-over trial was conducted with sixty-eight women with a self-reported history of straining during bowel movements or hard or lumpy stools in the past 2 years. As per regulatory requirements for probiotic studies, eligible women were generally healthy and not actively constipated at the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The third study did not provide a between‐group statistical analysis; however, the decrease in constipation frequency score was approximately twofold greater in the probiotic groups than in the placebo group . Four studies reported no significant effect of 4 different probiotic treatments; however, 1 of these studies showed a nonsignificant trend in favour of probiotics . Of the 7 studies, 5 had been published since the original consensus.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The third study did not provide a between‐group statistical analysis; however, the decrease in constipation frequency score was approximately twofold greater in the probiotic groups than in the placebo group . Four studies reported no significant effect of 4 different probiotic treatments; however, 1 of these studies showed a nonsignificant trend in favour of probiotics . Of the 7 studies, 5 had been published since the original consensus.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the 70 studies (Table S1) focused on IBS (based on Rome I, II or III criteria or physician diagnosis; 34 studies), antibiotic‐associated diarrhoea (13 studies) or diarrhoea‐associated Helicobacter pylori eradication therapy (7 studies). Other conditions were investigated in 16 studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations